2018
DOI: 10.4315/0362-028x.jfp-17-344
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Temperature, Moisture Content, and Physical Impurities on the Distribution and Survival of Salmonella enterica in Poultry Fat Intended for Pet Food Use

Abstract: Contamination of rendered products with Salmonella is a concern for the rendering industry, particularly when those products are intended for use in other foodstuffs, such as pet food. This study was conducted to understand the influence of compositional variation on the location and survivability of Salmonella in a poultry fat matrix. Specifically, this study aimed to (i) assess the influence of postinoculation time and moisture content on the distribution of Salmonella in rendered poultry fat and (ii) evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…However, when poultry fat was stored at 48°C and inoculated with high levels of Salmonella spp., bacterial decrease was easier in samples containing greater moisture. Our findings differ from those reported by ( Kiel, 2018 ), who showed poultry fat with higher levels of moisture had greater Salmonella growth over time. In the Kiel study, poultry fat was stored at lower temperatures (25°C) and varying levels of impurities.…”
Section: Discussioncontrasting
confidence: 99%
“…However, when poultry fat was stored at 48°C and inoculated with high levels of Salmonella spp., bacterial decrease was easier in samples containing greater moisture. Our findings differ from those reported by ( Kiel, 2018 ), who showed poultry fat with higher levels of moisture had greater Salmonella growth over time. In the Kiel study, poultry fat was stored at lower temperatures (25°C) and varying levels of impurities.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is similar to that of Trinetta et al (26), in whose study the Salmonella cocktail remained constant for up to 6 days when 5.5% (v/w) of liquid inoculum was added in rendered chicken fat. Kiel et al (16) reported a sharp decline (from~7 log to~1 log) in the Salmonella population in rendered chicken fat when 3% moisture was incorporated and after storage at 458C for 48 h. The recovery procedure of Salmonella in their study also differs from ours; we analyzed the fat phase and aqueous phase separately to mimic one potential industry scenario for bulk fat storage and (or) transportation.…”
Section: Resultsmentioning
confidence: 87%
“…The dry and wet inoculation methods have significant influence on the survival of Salmonella (18,27). Unlike previous reports (8,16,26), in this study we used dry inoculum and dry antimicrobial without any external added moisture in rendered fat. This method could be a more practical approach to study the viability of Salmonella in a fat system that contains low, or no, moisture.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of respondents reported storing their pet food against FDA and most manufacturers’ recommendations, which may have implications as far as increased risk of microbial contamination [ 17 ], nutritional degradation [ 18 ] and palatability. In addition, some respondents were engaging in behaviors that may increase risk of bacterial contamination that were not addressed in FDA guidelines such as the location of food preparation and storage.…”
Section: Discussionmentioning
confidence: 99%